2019
DOI: 10.1038/s41598-019-39854-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation tolerant padlock probe design for multiplexed detection of hypervariable RNA viruses

Abstract: The establishment of a robust detection platform for RNA viruses still remains a challenge in molecular diagnostics due to their high mutation rates. Newcastle disease virus (NDV) is one such RNA avian virus with a hypervariable genome and multiple genotypes. Classical approaches like virus isolation, serology, immunoassays and RT-PCR are cumbersome, and limited in terms of specificity and sensitivity. Padlock probes (PLPs) are known for allowing the detection of multiple nucleic acid targets with high specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…In another study, Ciftci et al showed that traditional approaches like virus isolation, serology, immunoassays, and RT‐PCR are difficult and limited in terms of specificity and sensitivity for detecting RNA viruses. However, rolling circle amplification, in combination with padlock probes, had a higher specificity for detecting RNA viruses like Newcastle disease virus, avian coronavirus, and avian influenza virus 78 …”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…In another study, Ciftci et al showed that traditional approaches like virus isolation, serology, immunoassays, and RT‐PCR are difficult and limited in terms of specificity and sensitivity for detecting RNA viruses. However, rolling circle amplification, in combination with padlock probes, had a higher specificity for detecting RNA viruses like Newcastle disease virus, avian coronavirus, and avian influenza virus 78 …”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…Other molecular techniques, such as loop-mediated isothermal amplification (LAMP) and padlock probes (PLPs) combined with rolling circle amplification (RCA), have been validated for IBV detection [ 78 , 79 ]. Additionally, NGS techniques have recently been used to study IBV [ 80 , 81 ].…”
Section: Approaches To Ibv Diagnosismentioning
confidence: 99%
“…These techniques include, but are not limited to, nucleic acid sequence-based amplification (NASBA), transcription-mediated amplification (TMA), self-sustained sequence replication (3SR), helicase-dependent amplification (HDA), rolling-circle amplification (RCA), signal-mediated amplification of RNA technology (SMART), strand-displacement amplification (SDA), recombinase polymerase amplification (RPA), and loop-mediated isothermal amplification (LAMP), which is probably the most well-known of these techniques [ 163 , 164 ]. Generally, the above-mentioned techniques target specific and unique sequences of DNA [ 22 , 165 ] or RNA [ 166 , 167 ] and in many cases, microRNA (miRNA) [ 168 , 169 , 170 ]. Paper-based nucleic acid amplification and detection are useful in diseases diagnosis [ 22 , 23 ], forensic analysis [ 171 ], food [ 172 ] and beverage [ 173 ] control, and environmental testing [ 165 ].…”
Section: Applications Of µPadsmentioning
confidence: 99%